Optimalisasi Kinerja Lembaga Ombudsman Daerah Istimewa Yogyakarta Dalam Penyadaran Hak Masyarakat Atas Pelayanan Publik - Arif Wicaksono; Suranto Suranto (Journal of Governance and Public Policy, 2014)
The Ombudsman Institution is an independent institution which functions to supervise the public seissues. The existence of  this institution is considered important to increase the public service especservice performance by the government or local government and its existence is guaranteed by law.progress reaches the provincial level and the This research uses the qualitative research method. Tincluding the primary and secondary data. The primary data covers interview and observation datondary data covers literature data and documentation. The analysis unit of  this research is the Ombof  Yogyakarta Special Region with the interviewed research subjects such as the Head, InstitutioSocialization, Cooperation, and Networking Unit, and Socialization Executive Assistant. The findingshows that the establishment of  The Governor Regulation Number 69 Year 2014 about the OrganizProcedure of  the Ombudsman Institution of  Yogyakarta Special Region causes the incorporation of Regional Ombudsman Institution (LOD) and the Private Ombudsman Institution (LOS), to be a singlas the Ombudsman Institution of  Yogyakarta Special Region and it was started in 2015. The OmbudYogyakarta Special Region performance optimization has been seen in its achievements which are ithe applicable regulations. The optimization of  socialization  task on public right awareness toward pby the Ombudsman Institution of  Yogyakarta Special Region is considered good and optimum. It canprograms done in the socialization intensity, socialization quality, and socialization portion comparties. The factors influencing the Ombudsman Institution of  Yogyakarta Special Region performancecovering the executive human resources factor, facilities and infrastructure and public participation